Prevalence and characteristics of e-cigarette users among the current smokers and ex-smokers population in Malaysia - Ho, Bee Kiau; Nik Mohamed, Mohamad Haniki; Ab Rahman, Jamalludin; Draman, Samsul; Kartiwi, Mira; Ab Rahman, Norny Syafinaz; Md Haris Robson, Noor Zurani; Chan, Caryn Mei Hsien; Lim, Kuang Hock; Baharom, Nizam; Ismail, Norliana; Tee, Guat Hiong; et al. (Malaysia Medical Association, 2017)
Data are limited on the extent and characteristics of electronic cigarettes (e-cigarettes) use among smokers and ex-smokers. The objectives of the study were to determine the prevalence of e-cigarette use, socio-demographic and smoking characteristics associated with current e-cigarette use among smokers and ex-smokers population in Malaysia. METHODS: This was an analysis of secondary data from a cross-sectional national population based e-cigarette study conducted in May and June 2016 throughout Malaysia. The details description of the sampling methods was described in National E-cigarette Survey (NECS) 2016 report. Briefly, data were obtained from the 1396 ever smokers i.e., 957 (68.6%) current smokers and 439 (31.4%) ex-smokers from this survey. RESULTS: Current e-cigarette use was found predominantly among current smokers (8.0%) as compared with ex-smokers (4.3%). Among current smokers, the reason for smoking e-cigarette was mainly wanting to try (44.7%), followed by intention to quit tobacco smoking (15.8%), to reduce tobacco smoking (10.5%), to replace tobacco smoking (7.9%) and to reduce cost of smoking (6.6%). There was no significant difference between the 2 groups in term of reasons for initiating e-cigarette. By using multiple logistic regressions analysis, we found that among current smokers, current e-cigarette users were more likely to be younger i.e., 18-44 years (aOR 4.83, 95%CI 1.97-11.86, p=0.001), urban residents (aOR 1.89, 95%CI 1.15-3.11, p=0.012), single/ divorced/ widowed (aOR 2.11, 95%CI 1.24-3.61, p=0.006) and student (aOR 2.25, 95%CI 1.01-5.01, p=0.048).